Reducing sewing defects to increase productivity in the apparel industry of Bangladesh by integrating lean methodology - Md. Limonur Lingkon; Pronab Saha; Abdulla Al Manzid; Md. Hasan; Showra Mahalanobish (International Journal of Research in Industrial Engineering)
The purpose of this study is to determine how the Bangladeshi garment industry's sewing defect reduction and productivity enhancement are affected by the Plan, Do, Check, Act (PDCA) and 5S (Sort, Set in order, Shine, Standardize, Sustain) techniques. One of the main reasons for production delays and increased costs is sewing defects. By reducing defects, improving  Overall Equipment Effectiveness (OEE), and methodically using integrated PDCA concepts, the study aims to streamline and expand the production flowline while increasing throughput. To continuously evaluate and improve the sewing process, the 5S method is also employed. Tools like cause-effect diagrams and Pareto charts were used to identify the defect correctly. The OEE was used to evaluate the actual efficiency. The integration of 5S and PDCA as a lean methodology was utilized to minimize the defect rate and maximize quality to improve efficiency. For this purpose, data was collected from some renowned factories in Bangladesh. This mixed-integrated methodology is used in the study to integrate quantitative defect analysis with worker satisfaction along with efficiency surveys. The findings should offer valuable insights to the RMG industry in Bangladesh, as producers seek sustainable methods to increase productivity and enhance product quality while mitigating the impact of sewing errors on their production procedures. OEE was increased by almost 3-4% through this research.